2000
DOI: 10.1074/jbc.275.13.9193
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing Hormone Receptor Initiates Multiple Signaling Pathways by Exclusively Coupling to Gq/11Proteins

Abstract: The agonist-bound gonadotropin-releasing hormone (GnRH) receptor engages several distinct signaling cascades, and it has recently been proposed that coupling of a single type of receptor to multiple G proteins (G q , G s , and G i ) is responsible for this behavior. GnRH-dependent signaling was studied in gonadotropic ␣T3-1 cells endogenously expressing the murine receptor and in CHO-K1 (CHO#3) and COS-7 cells transfected with the human GnRH receptor cDNA. In all cell systems studied, GnRH-induced phospholipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 56 publications
1
73
0
Order By: Relevance
“…A Constitutively Active G␣ q Mutant Induces c-Fos and LH␤ Protein Expression Acutely in L␤T2 Cells-Previous studies have implicated the G q/11 proteins in GnRH signaling (18,19). To explore further the functional importance of G␣ q in GnRH induced-ERK activation, c-Fos and LH␤ protein expression in L␤T2 cells, we used recombinant adenovirus vectors expressing either wild-type (WT) or a constitutively active mutant (Q209L) G␣ q , or a control virus expressing ␤-galactosidase.…”
Section: Fig 1 Effect Of Ptx On Gnrh-induced Erk Activation and C-fmentioning
confidence: 99%
See 2 more Smart Citations
“…A Constitutively Active G␣ q Mutant Induces c-Fos and LH␤ Protein Expression Acutely in L␤T2 Cells-Previous studies have implicated the G q/11 proteins in GnRH signaling (18,19). To explore further the functional importance of G␣ q in GnRH induced-ERK activation, c-Fos and LH␤ protein expression in L␤T2 cells, we used recombinant adenovirus vectors expressing either wild-type (WT) or a constitutively active mutant (Q209L) G␣ q , or a control virus expressing ␤-galactosidase.…”
Section: Fig 1 Effect Of Ptx On Gnrh-induced Erk Activation and C-fmentioning
confidence: 99%
“…Similarly, in CHO-K1 and COS-7 cells expressing the human GnRH receptor, GnRH couples exclusively to the G q/11 family of G proteins (19). However, the GnRH receptor also couples to G s in primary pituitary cultures and G-GH3 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fos is known to transrepress the induction of many genes (21). Rgs2 is a GTPase-activating protein that down-regulates the activity of G␣ q (22), the major G-protein utilized by the GnRH receptor (23). The small G-protein gem (kir) has recently been reported to down-regulate L-type calcium channel function (24).…”
Section: Confirmation Of Gene Regulation By Real-time Pcr-mentioning
confidence: 99%
“…The GnRHR has been previously shown to be coupled to multiple G proteins during agonist activation, including G q , G 11 , G s , G i , G 14 , G 15 [3,4,[6][7][8]25] although some laboratories have suggested that such regulation are all secondary to G q/11 coupling [9]. Such a schema would limit the amount of information that the receptor might convey, of course.…”
Section: Introductionmentioning
confidence: 97%